Production of Acetaldehyde via Oxidative Dehydrogenation of Ethanol over AgLi/SiO2 Catalysts - Narawich Mukda; Chaowat Autthanit; Piyasan Praserthdam; Bunjerd Jongsomjit (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
Three AgLi/SiO2 catalysts containing different types of silica supports [small particle size (SPS), medium particle size (MPS) and large particle size (LPS)] were prepared by incipient wetness co-impregnation techniques and tested in oxidative dehydrogenation of ethanol into acetaldehyde. The catalysts were characterized and evaluated by various characterization techniques (e.g. XRD, N2 physisorption, SEM-EDX, UV-Visible spectroscopy, H2-TPR, and CO2-TPD). This study reveals that the catalyst with the best performance is AgLi/SiO2-LPS with a yield in acetaldehyde of 76.8% at 300 °C. The results obtained with the tested catalysts are discussed, and the reasons of performance improvement caused by the presence of the dispersion of active components, the interaction between active components and silica supports, the textural properties of catalysts and reducibility, are raised. Besides, the cooperation of redox properties (Agnδ+  cluster and Ag0) and weak basic density played a pivotal role in promoting the formation of acetaldehyde from ethanol oxidative dehydrogenation. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).